Multi-media occurrence, bioaccumulation, and exposure assessment of PFAS across a Midwestern U.S. State - Maria S. Sepúlveda; Lisa Brown; Staci L. Capozzi; Samantha C. Cullom; Jeffrey E. Dick; Daniel J. Foti; Ronaldo H. Franjul; Nicole L. Franklin; Jennifer L. Freeman; Carolina Gonzalez-Canas; Wanyue Hui; Yuxin Jiang; et al. (Environmental Research, 2026)

An open-source motion platform that replicates time synchronised internal and external patient motion for real-time image-guided radiotherapy - Alicja Kaczynska; Chris Kuban; Abbas Zahr; William Nixon; Paul Keall; Freeman Jin; Ann Yan; Daniel Mason; Maegan Stewart; Julia Johnson; Jonathan Hindmarsh; Chandrima Sengupta (Physical and Engineering Sciences in Medicine, 2026)
Real-time Image-guided Radiotherapy (IGRT) technologies aim to track intra-fractional tumour motion during delivery of high radiation doses to tumours. For the development and safe implementation of real-time IGRT technologies into the clinic, there is a need for robust and repeatable quality assurance (QA) devices. Motivated by this need, this work presents the development and characterisation of a novel time-synchronised motion platform designed for QA purposes of real-time IGRT technologies that perform combined internal and external patient motion monitoring. The Int ernal- E xternal R obotic Act uator (IntERAct) QA device was developed to integrate a 6-degree-of-freedom (6DoF) robotic arm with a 1-degree-of-freedom (1DoF) motion actuator, which replicate 6DoF internal tumour and 1DoF external surface movements, respectively. The IntERAct device was validated by performing tests which replicated patient-measured lung and liver motion traces on the 6DoF and 1DoF platforms. The device synchronised the internal and external motions to within 0.1 s with under two-millimetre geometric accuracy. The full details of the IntERAct device have been compiled into an open-source repository on GitHub for the medical physics community to use: https://github.com/Image-X-Institute/IntERAct .

Priorities, concerns, and potential compromises amongst urban forest stakeholders: international lessons from Aotearoa New Zealand - Thomas F. Carlin; Tim Barnard; Toby Chapman; Justin Morgenroth; Daniel R. Richards; Robyn Simcock; Jonathon Avery; Zoë Avery; Yvette Dickinson; Kate Elliot; Claire Freeman; Derek Hayes; et al. (Urban Ecosystems, 2025)
Urban forests provide numerous benefits including habitat for wildlife, improving human health, purifying air and water, and preventing and mitigating the effects of climate change. The need to protect and improve our urban forests will only increase as populations increase and cities densify and expand over time. However, urban forest establishment and maintenance is challenging due to a lack of effective policies, delays, lack of communication, inappropriate targets, and lack of recognition, disunity, or resourcing amongst stakeholders. Here we present the results from a joint urban forest symposium-workshop that sought to determine the priorities and challenges of different stakeholder groups in New Zealand, including arborists, ecologists, non-ecologist researchers, indigenous peoples, and planners. We synthesise these lessons as recommendations to improve urban forest planning, design, establishment, and minimise conflicts between stakeholder groups. While the highest priorities of each stakeholder group are fairly distinct, there are high levels of overlap in the general priorities and challenges they face in working towards advancing those priorities. We suggest a 3-phase framework to deliver progress that broadly considers (1) data collection, (2) policy development, and (3) resource development. We suggest this framework should be supported by continual monitoring and data sharing, an increased investment in green employment and education, and further recognition of urban foresters, indigenous communities, and ecologists. We suggest that an inclusive approach based on a shared understanding of forest values and removing barriers is most likely to result in long-term success.

Permeate fluxes from desalination of brines and produced waters: A reactive transport modeling study - Sergi Molins; Nicolas Spycher; Sarah M. Dischinger; Mostafa Nassr; Ji Yeon Lee; Jacob Johnston; Nils Tilton; Kristofer L. Gleason; Benny D. Freeman; William T. Stringfellow; Daniel J. Miller (Applied Geochemistry, 2025)

Pacific Northwest birds have shifted their abundances upslope in response to 30 years of warming temperatures - Benjamin G. Freeman; Harold N. Eyster; Julian M. Heavyside; Daniel A. Yip; Monica H. Mather; F. Louise Waterhouse (Ecology, 2025)
Mountain species are predicted to respond to warming temperatures by moving to higher elevations that remain relatively cool. Species can track warming by shifting their entire distributions upwards (the “escalator to extinction” hypothesis) or by increasing in abundance in the upper portion of their elevational range while maintaining stable elevational limits (the “upslope lean” hypothesis). Alternatively, mountain species may not change their abundance or distribution despite climate change (the “persist‐in‐place” hypothesis). Here we evaluate these three contrasting hypotheses by analyzing responses of breeding forest bird species to three decades of warming in southwestern British Columbia, Canada. Consistent with the upslope lean hypothesis, species' optimum elevations (elevations of highest abundance) increased by an average of 126 m, approximately tracking upslope movements in temperature isotherms. In contrast, species' elevational range limits were stable on average, contra the escalator to extinction hypothesis. Many individual species had stable distributions and abundances, and species with upslope abundance increases typically maintained stable abundances within the lower elevation portions of their range. Taken together, most species in our study region appear to be responding neutrally or favorably to warming temperatures. Nevertheless, one mountain species, the Canada Jay, Canada's national bird, is declining and vulnerable to the escalator to extinction within our study region. Overall, we emphasize the importance of empirical data—and abundance data in particular—when evaluating mountain species' vulnerability to climate change.

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Domestication and evolutionary histories of specialized gut symbionts across cephalotine ants - Christian Cabuslay; John T. Wertz; Benoît Béchade; Yi Hu; Sonali Braganza; Daniel Freeman; Shreyansh Pradhan; Maria Mukhanova; Scott Powell; Corrie Moreau; Jacob A. Russell (Molecular Ecology, 2024)
The evolution of animals and their gut symbionts is a complex phenomenon, obscured by lability and diversity. In social organisms, transmission of symbionts among relatives may yield systems with more stable associations. Here, we study the history of a social insect symbiosis involving cephalotine ants and their extracellular gut bacteria, which come predominantly from host‐specialized lineages. We perform multi‐locus phylogenetics for symbionts from nine bacterial orders, and map prior amplicon sequence data to lineage‐assigned symbiont genomes, studying distributions of rigorously defined symbionts across 20 host species. Based on monophyly and additional hypothesis testing, we estimate that these specialized gut bacteria belong to 18 distinct lineages, of which 15 have been successfully isolated and cultured. Several symbiont lineages showed evidence for domestication events that occurred later in cephalotine evolutionary history, and only one lineage was ubiquitously detected in all 20 host species and 48 colonies sampled with amplicon 16S rRNA sequencing. We found evidence for phylogenetically constrained distributions in four symbionts, suggesting historical or genetic impacts on community composition. Two lineages showed evidence for frequent intra‐lineage co‐infections, highlighting the potential for niche divergence after initial domestication. Nearly all symbionts showed evidence for occasional host switching, but four may, more often, co‐diversify with their hosts. Through our further assessment of symbiont localization and genomic functional profiles, we demonstrate distinct niches for symbionts with shared evolutionary histories, prompting further questions on the forces underlying the evolution of hosts and their gut microbiomes.

The acute effects of cannabis, with and without cannabidiol, on attentional bias to cannabis related cues: a randomised, double-blind, placebo-controlled, cross-over study - Daniel Hall; Will Lawn; Shelan Ofori; Katie Trinci; Anya Borissova; Claire Mokrysz; Kat Petrilli; Michael A. P. Bloomfield; Matthew B. Wall; Tom P. Freeman; H. Valerie Curran (Psychopharmacology, 2024)
Rationale Attentional bias to drug-related stimuli is hypothesised to contribute towards addiction. However, the acute effects of Δ9-tetrahydrocannabinol (THC) on attentional bias to cannabis cues, the differential response in adults and adolescents, and the moderating effect of cannabidiol (CBD) are unknown. Objectives Our study investigated (1) the acute effects of vaporised cannabis on attentional bias to cannabis-related images in adults and adolescents and (2) the moderating influences of age and CBD. Methods We conducted a randomised, double-blind, placebo-controlled, cross-over study where three weight-adjusted vaporised cannabis preparations: ‘THC’ (8 mg THC for a 75-kg person), ‘THC + CBD’ (8 mg THC and 24 mg CBD for a 75-kg person) and PLA (matched placebo). Cannabis was administered on 3 separate days to 48 participants, who used cannabis 0.5–3 days/week: 24 adolescents (12 females, aged 16–17) and 24 adults (12 females, aged 26–29). Participants completed a visual probe task with cannabis cues. Our primary outcome was attentional bias to cannabis stimuli, measured using the differential reaction time to a cannabis vs. neutral probe, on 200-ms trials. Results In contrast to hypotheses, attention was directed away from cannabis cues on placebo, and there was a main effect of the drug ( F (2,92) = 3.865, p = 0.024, η 2 p = 0.077), indicating THC administration eliminated this bias. There was no significant impact of CBD nor an age-by-drug interaction. Conclusions Acute THC intoxication eliminated attentional bias away from cannabis cues. There was no evidence of differential response in adolescents compared to adults and no evidence that a moderate vaporised dose of CBD altered the impact of cannabis on attentional bias. Trial registration This study was listed with the US National Library of Medicine and registered on ClinicalTrials.gov, URL: Do Adolescents and Adults Differ in Their Acute Response to Cannabis?—Full Text View—ClinicalTrials.gov , registration number: NCT04851392.

The socioecological benefits and consequences of oil palm cultivation in its native range: The Sustainable Oil Palm in West Africa (SOPWA) Project - Michael D. Pashkevich; Cicely A.M. Marshall; Benedictus Freeman; Valentine J. Reiss-Woolever; Jean-Pierre Caliman; Julia Drewer; Becky Heath; Matthew T. Hendren; Ari Saputra; Jake Stone; Jonathan H. Timperley; William Draper; et al. (Science of The Total Environment, 2024)

Correction to: Black twig borer and other ambrosia and bark beetles in Israel - Zvi Mendel; Stanley Freeman; Jiri Hulcr; Etan Recht; Gal Zagron; Allon Bear; Laor Orshan; Shahar Samra; Omer Golan; Margareta Walczak; Miriam Silberstein; Shai Golani; et al. (Phytoparasitica, 2023)

The Use of Collagen Methacrylate in Actuating Polyethylene Glycol Diacrylate–Acrylic Acid Scaffolds for Muscle Regeneration - Yoliem S. Miranda Alarcón; Dorota Jazwinska; Terrence Lymon; Amin Khalili; Daniel Browe; Brandon Newton; Michael Pellegrini; Rick I. Cohen; David I. Shreiber; Joseph W. Freeman (Annals of Biomedical Engineering, 2023)

Host phylogeny and elevation predict infection by avian haemosporidians in a diverse New Guinean bird community - Geoffrey C. F. Lau; Alexandra M. Class Freeman; Paulo Pulgarín‐R; Carlos Daniel Cadena; Robert E. Ricklefs; Benjamin G. Freeman (Journal of Biogeography, 2023)
Aim The biotic interactions hypothesis predicts that interactions between species are stronger at lower elevations compared to higher elevations. We tested whether this prediction is met by examining elevational patterns in avian haemosporidian infections in New Guinean birds. Location YUS Conservation Area, Papua New Guinea. Taxon Birds and haemosporidia. Methods We collected blood samples from 2268 individuals of 66 bird species along a reef‐to‐ridgetop tropical elevational gradient covering ~3000 m of elevation. We used molecular methods to screen samples for haemosporidian parasites, and sequenced 70% of positive infections to determine the identity of parasite genera. We fit a phylogenetic generalized mixed‐effects model to test whether infection prevalence was higher at low elevations, as predicted by the biotic interactions hypothesis. Finally, we tested for phylogenetic signal in parasite prevalence and in host elevational distribution using Pagel's λ . Results Overall parasite prevalence was 45% . Infection prevalence decreased with elevation, though prevalence remained above ~30% even for high‐elevation communities between 2000 and 3000 m. We found strong phylogenetic signal in infection prevalence, but no phylogenetic signal in host elevational distribution. Nearly all sequenced infections (97%) were of Haemoproteus. Main Conclusions Our results are consistent with predictions arising from the biotic interactions hypothesis. However, phylogenetic relationships among hosts are a much better predictor of infection prevalence than is elevational position: closely related bird species tend to have similar infection prevalence regardless of the elevations where they live.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Assessing awareness on biodiversity conservation among Nigerians: the Aichi Biodiversity Target 1 - Emmanuel O. Akindele; Michael C. Ekwemuka; Paul Apeverga; Tajudeen O. Amusa; Samuel Olajuyigbe; Oluwakayode M. Coker; Fatsuma Olaleru; Michelle Fasona; Elizabeth N. Usen; Abubakar S. Ringim; Opeyemi A. Adedoja; Chinedu C. Nsude; et al. (Biodiversity and Conservation, 2021)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Impacts of Urbanization and Development on Estuarine Ecosystems and Water Quality - Lauren A. Freeman; D. Reide Corbett; Allison M. Fitzgerald; Daniel A. Lemley; Antonietta Quigg; Cecily N. Steppe (Estuaries and Coasts, 2019)

The buzz segment of Savannah sparrow song is a population marker - Heather Williams; Clint W. Robins; D. Ryan Norris; Amy E. M. Newman; Corey R. Freeman-Gallant; Nathaniel T. Wheelwright; Daniel J. Mennill (Journal of Ornithology, 2019)

Toxicity, recovery, and resilience in a 3D dopaminergic neuronal in vitro model exposed to rotenone - Georgina Harris; Melanie Eschment; Sebastian Perez Orozco; J. Michael McCaffery; Richard Maclennan; Daniel Severin; Marcel Leist; Andre Kleensang; David Pamies; Alexandra Maertens; Helena T. Hogberg; Dana Freeman; et al. (Archives of Toxicology, 2018)

Proceedings of the third international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Timothy R. Rebbeck; Reiko Nishihara; Andrew H. Beck; Colin B. Begg; Alexei A. Bogdanov; Yin Cao; Helen G. Coleman; Gordon J. Freeman; Yujing J. Heng; Curtis Huttenhower; Rafael A. Irizarry; et al. (Cancer Causes & Control, 2017)

The neuronal metabolite NAA regulates histone H3 methylation in oligodendrocytes and myelin lipid composition - N. K. Singhal; H. Huang; S. Li; R. Clements; J. Gadd; A. Daniels; E. E. Kooijman; P. Bannerman; T. Burns; F. Guo; D. Pleasure; E. Freeman; et al. (Experimental Brain Research, 2017)

Invasive Asian Fusarium – Euwallacea ambrosia beetle mutualists pose a serious threat to forests, urban landscapes and the avocado industry - Kerry O’Donnell; Ran Libeskind-Hadas; Jiri Hulcr; Craig Bateman; Matthew T. Kasson; Randy C. Ploetz; Joshua L. Konkol; Jill N. Ploetz; Daniel Carrillo; Alina Campbell; Rita E. Duncan; Pradeepa N. H. Liyanage; et al. (Phytoparasitica, 2016)

An amniote life‐history database to perform comparative analyses with birds, mammals, and reptiles - Nathan P. Myhrvold; Elita Baldridge; Benjamin Chan; Dhileep Sivam; Daniel L. Freeman; S. K. Morgan Ernest (Ecology, 2015)
Studying life‐history traits within and across taxonomic classifications has revealed many interesting and important patterns, but this approach to life history requires access to large compilations of data containing many different life‐history parameters. Currently, life‐history data for amniotes (birds, mammals, and reptiles) are split among a variety of publicly available databases, data tables embedded in individual papers and books, and species‐specific studies by experts. Using data from this wide range of sources is a challenge for conducting macroecological studies because of a lack of standardization in taxonomic classifications, parameter values, and even in which parameters are reported. In order to facilitate comparative analyses between amniote life‐history data, we created a database compiled from peer‐reviewed studies on individual species, macroecological studies of multiple species, existing life‐history databases, and other aggregated sources as well as published books and other compilations. First, we extracted and aggregated the raw data from the aforementioned sources. Next, we resolved spelling errors and other formatting inconsistencies in species names through a number of computational and manual methods. Once this was completed, subspecies‐level data and species‐level data were shared via a data‐sharing algorithm to accommodate the variety of species transformations (taxonomic promotions, demotions, merges, divergences, etc.) that have occurred over time. Finally, in species where multiple raw data points were identified for a given parameter, we report the median value. Here, we report a normalized and consolidated database of up to 29 life‐history parameters, containing at least one life‐history parameter for 21 322 species of birds, mammals, and reptiles.

The Role of Women in Water Management and Conflict Resolution in Marsabit, Kenya - Sarah Yerian; Monique Hennink; Leslie E. Greene; Daniel Kiptugen; Jared Buri; Matthew C. Freeman (Environmental Management, 2014)

Eyeblink Conditioning in Healthy Adults: A Positron Emission Tomography Study - Krystal L. Parker; Nancy C. Andreasen; Dawei Liu; John H. Freeman; Laura L. Boles Ponto; Daniel S. O’Leary (The Cerebellum, 2012)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Prefrontal Dopaminergic and Enkephalinergic Synaptic Accommodation in HIV-associated Neurocognitive Disorders and Encephalitis - Benjamin B. Gelman; Joshua G. Lisinicchia; Tianshen Chen; Kenneth M. Johnson; Kristofer Jennings; Daniel H. Freeman; Vicki M. Soukup (Journal of Neuroimmune Pharmacology, 2012)

An ice‐core proxy for northerly air mass incursions into West Antarctica - Daniel A. Dixon; Paul A. Mayewski; Ian D. Goodwin; Gareth J. Marshall; Rhaelene Freeman; Kirk A. Maasch; Sharon B. Sneed (International Journal of Climatology, 2012)
A 200‐year proxy for northerly air mass incursions (NAMI) into central and western West Antarctica is developed from the examination of 19 shallow (21–150 m deep) Antarctic ice‐core non‐sea‐salt (nss) Ca 2+ concentration records. The NAMI proxy reveals a significant rise in recent decades. This rise is unprecedented for at least the past 200 years and is coincident with anthropogenically driven changes in other large‐scale Southern Hemisphere (SH) environmental phenomena such as greenhouse gas (GHG) induced warming, ozone depletion, and the associated intensification of the SH westerlies. The Hysplit trajectory model is used to examine air mass transport pathways into West Antarctica. Empirical orthogonal function analysis, in combination with trajectory results, suggests that atmospheric circulation is the dominant factor affecting nssCa 2+ concentrations throughout central and western West Antarctica. Ozone recovery will likely weaken the spring‐summer SH westerlies in the future. Consequently, Antarctica could lose one of its best defences against SH GHG warming. Copyright © 2011 Royal Meteorological Society

Does concentrating chemical defenses within specific regions of marine sponges result in enhanced protection from predators? - Christopher J. Freeman; Daniel F. Gleason (Hydrobiologia, 2012)

Chemical Signals of Elephant Musth: Temporal Aspects of Microbially-Mediated Modifications - Thomas E. Goodwin; Laura J. Broederdorf; Blake A. Burkert; Innocent H. Hirwa; Daniel B. Mark; Zach J. Waldrip; Randall A. Kopper; Mark V. Sutherland; Elizabeth W. Freeman; Julie A. Hollister-Smith; Bruce A. Schulte (Journal of Chemical Ecology, 2012)

Cellular correlates of anxiety in CA1 hippocampal pyramidal cells of 5-HT1A receptor knockout mice - Emily Freeman-Daniels; Sheryl G. Beck; Lynn G. Kirby (Psychopharmacology, 2011)

Chemical defenses, nutritional quality, and structural components in three sponge species: Ircinia felix, I. campana, and Aplysina fulva - Christopher J. Freeman; Daniel F. Gleason (Marine Biology, 2010)

Leptin blockade attenuates sodium excretion in saline-loaded normotensive rats - Daniel Villarreal; Garry Reams; Ronald Freeman; Robert Spear; Inna Tchoukina; Huma Samar (Molecular and Cellular Biochemistry, 2006)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Molecular characterisation of a NADH ubiquinone oxidoreductase subunit 5 from Schistosoma mansoni and inhibition of mitochondrial respiratory chain function by testosterone - Marcelo Rosado Fantappié; Antônio Galina; Ricardo Luís de Mendonça; Daniel Rodrigues Furtado; W. Evan Secor; Daniel G. Colley; Rodrigo Corrêa-Oliveira; George Freeman; Antônio Jorge Tempone; Lia Lannes de Camargo; Franklin David Rumjanek (Molecular and Cellular Biochemistry, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)